Delineating Human B Cell Precursor Development With Genetically Identified PID Cases as a Model - Wentink, Marjolein W. J.; Kalina, Tomas; Perez-Andres, Martin; del Pino Molina, Lucia; IJspeert, Hanna; Kavelaars, François G.; Lankester, Arjan C.; Lecrevisse, Quentin; van Dongen, Jacques J. M.; Orfao, Alberto; van der Burg, Mirjam (Frontiers in Immunology, 2019)
B-cell precursors (BCP) arise from hematopoietic stem cells in bone marrow (BM). Identification and characterization of the different BCP subsets has contributed to the understanding of normal B-cell development. BCP first rearrange their immunoglobulin (Ig) heavy chain (IGH) genes to form the pre-B-cell receptor (pre-BCR) complex together with surrogate light chains. Appropriate signaling via this pre-BCR complex is followed by rearrangement of the Ig light chain genes, resulting in the formation, and selection of functional BCR molecules. Consecutive production, expression, and functional selection of the pre-BCR and BCR complexes guide the BCP differentiation process that coincides with corresponding immunophenotypic changes. We studied BCP differentiation in human BM samples from healthy controls and patients with a known genetic defect in V(D)J recombination or pre-BCR signaling to unravel normal immunophenotypic changes and to determine the effect of differentiation blocks caused by the specific genetic defects. Accordingly, we designed a 10-color antibody panel to study human BCP development in BM by flow cytometry, which allows identification of classical preB-I, preB-II, and mature B-cells as defined via BCR-related markers with further characterization by additional markers. We observed heterogeneous phenotypes associated with more than one B-cell maturation pathway, particularly for the preB-I and preB-II stages in which V(D)J recombination takes place, with asynchronous marker expression patterns. Next Generation Sequencing of complete IGH gene rearrangements in sorted BCP subsets unraveled their rearrangement status, indicating that BCP differentiation does not follow a single linear pathway. In conclusion, B-cell development in human BM is not a linear process, but a rather complex network of parallel pathways dictated by V(D)J-recombination-driven checkpoints and pre-BCR/BCR mediated-signaling occurring during B-cell production and selection. It can also be described as asynchronous, because precursor B-cells do not differentiate as full population between the different stages, but rather transit as a continuum, which seems influenced (in part) by V-D-J recombination-driven checkpoints.